Effects of Δ(9)-tetrahydrocannabinol (THC) on human amniotic epithelial cell proliferation and migration. (1st February 2018) - Yao, J.L.; He, Q.Z.; Liu, M.; Chang, X.W.; Wu, J.T.; Duan, T.; Wang, K.
Abstract: Background: The deleterious effects of cannabis consumption for fertility and pregnancy outcome are recognized for years. The main psychoactive molecule of cannabis, Δ(9)-tetrahydrocannabinol (THC) is able to cross the placenta barrier and cause alterations in fetal growth, low birth weight and preterm labor. However, the effects of THC on the human placenta amnion are still unknown. Methods: The distributions of CB1R and CB2R in human amnion tissues were observed by immunohistochemistry (IHC). Human amniotic epithelial cell proliferation and migration in response to THC treatment were measured by MTS and transwell assays, respectively. The PCR array was performed to study the key regulators involved in the cell migration. The protein levels of CB1R, CB2R in amnion tissues and MMP2, MMP9 in cells were detected by western blotting. Small interfering RNAs (siRNAs) were used to knockdown MMP2 and MMP9 in WISH cells. Results: Our results indicated that both CB1R and CB2R primarily identified in the epithelial layer of human placental amnion tissue. The CB1R expression in the amnion tissue was higher in the preterm group than normal control. High-dose of THC (30uM, but not 20 and 10uM) significantly inhibited (p < 0.01) human amniotic epithelial cell lines (WISH) proliferation. Meanwhile, THC at both 10uM and 20uM (p < 0.05) significantly suppressed cells migration in both WISH and primary human amniotic epithelial cells. The PCR array data and siRNA experiments demonstrated that MMP2/9 were tightly involved in the regulation of THC-inhibited cell migration in WISH cells. Conclusion: These results suggested that THC inhibited the migration of human amniotic epithelial cell through the regulation of MMP2 and MMP9, which in turn altered the development of the amnion during the gestation and partially resulted in preterm labor and other adverse pregnancy outcomes.